Iklim Komunikasi Organisasi Pada Kantor Balai Sertifikasi dan Perbenihan Tanaman Hutan - Meliza Putri Darudono; Nadia Itona Siregar (STIE Wiyatamandala, 2023)
A good communication climate supports the creation of organizational effectiveness. The communication climate will affect the behavior of its members, both the relationship between superiors, subordinates and co-workers. One of the organizational institutions that has attempted to carry out organizational communication in order to achieve organizational effectiveness is the Center for Certification and Seeds of Forest Plants. At this agency there are problems in the work environment and there is miss communication at work. Special attention to the existence of employees can be done such as establishing good relationships in order to create a sense of trust, honesty, openness of communication, and listening in good communication with superiors, subordinates and co-workers. The purpose of this study was to find out how the organizational communication climate was at the Office of the Forest Plant Seed Certification and Seed. The research method used is descriptive statistics. The sample used was 55 employees. The results showed that the organizational communication climate at the Forest Plant Seed Certification and Seed Center was classified as Good. This is because the majority of male employees show a high degree of openness in communication compared to women, such as the ease with which they can coordinate with co-workers in a flexible manner and have confidence in the ability of themselves and co-workers to complete work. The conclusion of this study is that the organizational communication climate at the Forest Plant Seed Certification and Seed Center is conducive.